Fictionalism in philosophy - Armour-Garb, Bradley P., 1968-; Kroon, Fred (New York : Oxford University Press, 2020)
"Within contemporary, analytic philosophy, "Fictionalism"-broadly understood as a view that uses a notion of fiction in order to resolve certain philosophical problems that do not necessarily have anything to do with fiction-has been on the scene for some time. There is a well-known collection, Fictionalism in Metaphysics (OUP, 2005), which provided a good indication of the scope of the view (and its problems) as things stood in the early 2000's. But more than a decade has passed since the appearance of that volume, and much has happened in philosophy, including in the area of fictionalism. In addition to the fact that fictionalism in philosophy appears to be more popular than ever, there are now competing views about how to tackle some of the issues that fictionalists aim to address. Moreover, fictionalism has branched out into many more areas, and there is a continuing debate about what fictionalism in philosophy actually amounts to, and about how precisely it ought to be pursued. There is thus a pressing need for a volume such as Fictionalism in Philosophy. After a detailed discussion in the book's introductory chapter of how, in the light of these ongoing debates, philosophers should think of fictionalism and its connection to metaontology more generally, the remaining chapters provide readers with some of the most current and up-to-date work on fictionalism, both for and against. As such, the volume will be of interest to professional philosophers, as well as to graduate students in philosophy and to advanced undergraduates"--
Includes bibliographical references and index.
Keywords: Fictions, Theory of; Philosophy